2010
DOI: 10.21608/jfds.2010.82504
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Yoghurt Fortified With Different Zinc Salts

Abstract: Fresh buffalo's milk of 6% fat was heated. Each of three zinc salts (Zinc gluconate, zinc sulphate and zinc acetate) was added to individual milk sample at levels of 30 mg Zn/L milk with the addition to the control treatment. Then, cooled, and inoculcated with 3% mixed culture of Lactobacillus delbrueckii sub sp. bulgaricus and Streptococcus salivarius sub sp thermophilus. and incubated at 42°C until firm curd was formed at pH 4.6. The resultant yogurt was kept in refrigerator (6±1°C) for 10 days. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Titratable acidity (%) of both control and fortified samples was 0.80% and 0.79% on 1 st day. After 10 days, titratable acidity of control and fortified samples increased to 0.89% and 0.85%, respectively, which is analogous with El-Sabie et al, (2010), who reported an increase in acidity of control and fortified samples to 1.19% and 0.85%, respectively. Al-Shaikh, (2020) also observed an increase up to 0.90% and 0.87% for control and Zinc fortified yogurt, respectively, for 14 days storage.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Titratable acidity (%) of both control and fortified samples was 0.80% and 0.79% on 1 st day. After 10 days, titratable acidity of control and fortified samples increased to 0.89% and 0.85%, respectively, which is analogous with El-Sabie et al, (2010), who reported an increase in acidity of control and fortified samples to 1.19% and 0.85%, respectively. Al-Shaikh, (2020) also observed an increase up to 0.90% and 0.87% for control and Zinc fortified yogurt, respectively, for 14 days storage.…”
Section: Resultssupporting
confidence: 85%
“…This may be since a decrease in pH with time results in electrostatic attraction between caseins molecules which in turn causes reorganization of protein matrix and exudation of water (Lee & Lucy, 2010). El-Sabie et al, (2010) also reported decreased syneresis in zinc fortified yogurt samples as compared to control and increase in syneresis in all samples during 10 days of storage.…”
Section: Resultsmentioning
confidence: 68%